Method for synthesizing ammonia by electrochemically reducing nitrogen and biphase solid electrolyte used in method

By developing the perovskite biphasic solid electrolyte BCZY@YSZ, the problem of low efficiency of electrochemical synthesis of ammonia under normal temperature and pressure was solved, and efficient ammonia synthesis under relatively low temperature conditions was achieved, and the electrolyte had high temperature stability and mechanical properties.

CN119640285AActive Publication Date: 2025-03-18ZHEJIANG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411744837.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-18
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The efficiency of electrochemical synthesis of ammonia at room temperature and pressure is too low to achieve mass production, and high-temperature solid electrolytes have problems such as proton transfer rate, conductivity and thermal stability in the design and development.

Method used

A perovskite biphasic solid electrolyte BCZY@YSZ was developed, and a perovskite biphasic solid electrolyte was mixed and pre-fired by mixing and pre-firing the oxygen ion conductivity of YSZ, combining with the oxygen ion conductivity of YSZ, forming a composite electrolyte with high proton and oxygen ion conductivity.

Benefits of technology

It has achieved efficient electrochemical reduction of nitrogen in normal pressure of 200-500°C, with a reaction product conversion rate of 98%, and the unit yield of the product is improved. The electrolyte has excellent high temperature stability and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640285A_ABST
    Figure CN119640285A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new energy materials, and particularly discloses a double-phase solid electrolyte for synthesizing ammonia by electrochemical reduction of nitrogen, which is prepared by the following steps: uniformly mixing barium nitrate, cerium nitrate, zirconium nitrate and yttrium nitrate, crushing and pre-sintering to obtain BCZY powder; the preparation method comprises the following steps: doping Y2O3 into ZrO2, uniformly mixing, crushing and pre-sintering to obtain YSZ powder; and uniformly mixing the BCZY powder and the YSZ powder, carrying out mold pressing to prepare a green body, and sintering the green body at 1400-1500 DEG C for 10-12 hours to obtain the biphase solid electrolyte BCZY-YSZ. The invention also discloses a method for synthesizing ammonia by electrochemically reducing nitrogen by using the double-phase solid electrolyte as an electrolyte layer. According to the invention, long service life and reliability of the electrolyte can be ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy materials, and in particular relates to a perovskite solid electrolyte and a method for using the same for electrochemically reducing nitrogen to synthesize ammonia at low temperature and normal pressure. Background Art

[0002] The synthetic ammonia industry is of great significance to the national economy and social development. Ammonia is not only an important chemical product, but also an industrial raw material for the production of almost all nitrogen-containing compounds. It is widely used in fertilizers, transportation, refrigeration, plastics, pharmaceuticals, explosives and other fields. At present, the method used for industrial ammonia synthesis is still the Haber-Bosch ammonia synthesis method that was born in the early 20th century. However, this process has high equipment pressure requirements, complex process flow, low conversion rate (10% to 15%), high energy consumption, and serious environmental pollution.

[0003] In recent years, the electrochemical synthesis of ammonia has received widespread attention and research from scientific researchers. Electrochemical synthesis of ammonia can break the thermodynamic energy barrier of nitrogen activation under the action of electrical energy, remove the thermodynamic equilibrium limitation, and allow the nitrogen reduction reaction to proceed under relatively mild conditions. Aqueous electrolytes are usually used under normal temperature and pressure working conditions. Zang et al. (ACS Catalysis, 2019, 9(11): 10166-10173) developed a class of Cu single-atom catalysts NC-Cu SA based on a porous nitrogen-doped carbon network structure, and studied their catalytic performance for nitrogen reduction in alkaline and acidic solutions. In 0.1M KOH and 0.1M HCl electrolytes, the NH3 yields of NC-Cu SA were 53.3 and 0.1%, respectively. The FE is 13.8% and 11.7% respectively. Due to the relatively low operating temperature, the kinetic reaction rate is inevitably very slow at low temperatures. The use of solid electrolytes can solve the problem of slow kinetic reactions. Skodra et al. (Solid State Ionics, 2009, 180 (23 / 24 / 25): 1332-1336) used yttrium-stabilized zirconia (8 mol% YSZ) as an electrolyte and successfully synthesized ammonia using water vapor and nitrogen as raw materials. The reaction device worked at 500-700°C and an atmospheric pressure, but the conversion rates of steam and nitrogen into ammonia were very low, which was mainly due to the low proton flux and poor conductivity of the electrode.

[0004] According to existing literature and technology, electrochemical synthesis of ammonia is an environmentally friendly alternative to traditional ammonia synthesis. However, the process of synthesizing ammonia directly using nitrogen and water at room temperature and pressure is too inefficient to achieve mass production. The use of high-temperature solid electrolytes can liberate pressure conditions while maintaining a faster kinetic speed. The key lies in designing and developing electrolytes with high proton transfer rate, high conductivity and thermal stability.

[0005] Among the currently available solid electrolytes, BCZY and YSZ are only used as single-phase electrolytes, and YSZ has insufficient proton conductivity. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a dual-phase solid electrolyte (perovskite solid electrolyte) and a method for using the same to electrochemically reduce nitrogen to synthesize ammonia at relatively low temperature (200-500° C.) and normal pressure.

[0007] In order to solve the above technical problems, the present invention provides a two-phase solid electrolyte for electrochemical reduction of nitrogen to synthesize ammonia, comprising the following steps:

[0008] 1) According to the molar ratio of Ba:Ce:Zr:Y=1:x:y:1-xy, barium nitrate, cerium nitrate, zirconium nitrate and yttrium nitrate are uniformly mixed to obtain a mixture 1; x=0.1-0.9, y=0.1-0.9;

[0009] According to Y2O3:ZrO2=7-9mol% (preferably 8mol%), Y2O3 is added into ZrO2 and mixed uniformly to obtain a second mixture;

[0010] Instructions: Calculate the mass of each raw material based on the desired stoichiometric ratio;

[0011] 2) The mixture is crushed and finely ground (until it passes through a 200-mesh sieve) and then pre-calcined in air at 900-1000°C for 3-5h to obtain BCZY powder;

[0012] The mixture is crushed and finely divided (until it passes through a 200-mesh sieve) and pre-calcined in air at 900-1000°C for 3-5 hours to obtain YSZ powder;

[0013] illustrate:

[0014] After the mixture is pre-calcined, it can be further pulverized (until it passes through a 300-mesh sieve) to obtain BCZY powder;

[0015] After the pre-calcined mixture, the mixture can be further pulverized (until it passes a 300-mesh sieve) to obtain YSZ powder.

[0016] The above mixture is pre-burned to eliminate the volatile components (such as nitrogen oxides NO x ) and promote the initial reaction to form a perovskite phase and a stable zirconia phase;

[0017] 3) Mix BCZY powder and YSZ powder in a mass ratio of 1-5:5-1 to form a composite material precursor;

[0018] 4) The composite material precursor is molded into a green body, and then the molded green body is sintered in air at 1400-1500° C. for 10-12 hours to obtain a two-phase solid electrolyte (a dense two-phase electrolyte BCZY@YSZ).

[0019] The chemical formula of BCZY is BaCe x Zr y Y 1-x-y O3- δ , δ represents the proportion of oxygen vacancies in the compound, and 3-δ is the actual oxygen concentration. This is a conventional expression.

[0020] That is, the present invention obtains a new type of dual-phase electrolyte BCZY@YSZ, which combines the proton conductive material BaCe x Zr y Y 1-x-y O3- δ (BCZY) and oxygen ion conductive material Y2O3 doped ZrO2 (YSZ).

[0021] As an improvement of the dual-phase solid electrolyte of the present invention:

[0022] x=0.6~0.7, y=0.2~0.3;

[0023] BCZY powder:YSZ powder=mass ratio of 1 to 2:1.

[0024] As a further improvement of the dual-phase solid electrolyte of the present invention:

[0025] In step 1), the molar ratio of Ba:Ce:Zr:Y=1:0.7:0.2:0.1; Y2O3:ZrO2=8 mol%;

[0026] In step 2), the mixture 1 is crushed and pre-fired in air at 900° C. for 3 h, and the mixture 2 is crushed and pre-fired in air at 900° C. for 3 h.

[0027] As a further improvement of the dual-phase solid electrolyte of the present invention:

[0028] The pressure of compression molding is 100MPa to 200MPa.

[0029] The present invention also provides a method for synthesizing ammonia by electrochemical reduction of nitrogen, using a flat solid oxide fuel cell, the flat solid oxide fuel cell comprising a cathode layer, an anode layer and an electrolyte layer located between the cathode layer and the anode layer; the anode layer corresponds to the anode chamber of the battery, and the cathode layer corresponds to the cathode chamber of the battery; high-purity hydrogen (H2) is introduced into the anode chamber, high-purity nitrogen (N2) is introduced into the cathode chamber, and the generated ammonia (NH3) is collected in the cathode chamber;

[0030] The material of the electrolyte layer is a two-phase solid electrolyte;

[0031] The battery is heated and kept warm to 200-500°C using a high temperature furnace, and the voltage range of both ends of the battery is controlled to be 0-2.0V (preferably 1.2-1.5V) using a power supply;

[0032] Note: The gas in the cathode chamber passes through a condensing device, thereby condensing the ammonia into liquid or gaseous ammonia for collection.

[0033] As an improvement of the method for synthesizing ammonia by electrochemical reduction of nitrogen of the present invention:

[0034] The material of the anode layer is Ni / YSZ; the material of the cathode layer is Fe / YSZ.

[0035] As a further improvement of the method for synthesizing ammonia by electrochemical reduction of nitrogen of the present invention:

[0036] The thickness of the anode layer (Ni / YSZ) is 18 to 22 μm, the thickness of the electrolyte layer is 9 to 11 μm, and the thickness of the cathode layer (Fe / YSZ) is 18 to 22 μm.

[0037] The flow rates of hydrogen and nitrogen are 80-120 sccm, and the pressures are 1.1-1.3 atm (preferably, the flow rates are 100 sccm, and the pressures are 1.2 atm). By controlling the flow rate and pressure, a stable supply of gas is ensured.

[0038] As a further improvement of the method for synthesizing ammonia by electrochemical reduction of nitrogen of the present invention:

[0039] The dual-phase solid electrolyte (BCZY@YSZ) is prepared into a slurry, coated on the anode layer (Ni / YSZ), dried and sintered to form an electrolyte layer; then Fe / YSZ is prepared into a slurry and coated on the other side of the electrolyte layer, dried and sintered to form a cathode layer.

[0040] The present invention uses nitrogen and hydrogen as raw materials to develop a perovskite-type solid electrolyte with characteristics for electrochemical synthesis of ammonia under normal pressure.

[0041] Compared with the prior art, the present invention has the following advantages:

[0042] 1) A novel dual-phase electrolyte BCZY@YSZ is provided, which has both proton conductivity and oxygen ion conductivity, can conduct protons and oxygen ions more efficiently at high temperatures, exhibits lower resistance and higher reactivity, and thus improves the overall efficiency of the ammonia synthesis reaction.

[0043] The biphasic electrolyte BCZY@YSZ has both proton conductivity and oxygen ion conductivity, which can conduct protons and oxygen ions more efficiently at high temperatures and show lower resistance (electrode polarization impedance of 0.32Ω·cm 2 ) and higher reactivity, thereby improving the overall efficiency of the ammonia synthesis reaction.

[0044] 2) Both BCZY and YSZ have excellent high-temperature stability and are not easily decomposed or failed in high-temperature operating environments, thus ensuring the long-term service life and reliability of the electrolyte.

[0045] 3) The composite electrolyte material combines the mechanical strength of BCZY and YSZ, so it has good thermal shock resistance (no cracks and ruptures after 30 cycles) and mechanical properties (flexural strength 160MPa, compressive strength 460MPa), and can withstand high-temperature operation and repeated cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings.

[0047] Figure 1 This is a schematic diagram of the structure of the cathode layer, anode layer, and electrolyte layer of a flat solid oxide fuel cell. DETAILED DESCRIPTION

[0048] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process.

[0049] Example 1, BaCe 0.7 Zr 0.2 Y 0.1 O3- δ @YSZ preparation:

[0050] 1) Setting Ba:Ce:Zr:Y=1:0.7:0.2:0.1 (molar ratio), mixing barium nitrate, cerium nitrate, zirconium nitrate and yttrium nitrate to obtain a mixture 1;

[0051] According to Y2O3:ZrO2=8mol%, Y2O3 is doped into ZrO2 to obtain mixture 2;

[0052] 2) The mixture is first crushed and refined by a ball mill (until it passes a 200-mesh sieve) to ensure uniform mixing, and then pre-calcined at 900°C in air for 3 hours, and then the pre-calcined product is crushed by a ball mill (until it passes a 300-mesh sieve) to further refine the particles and improve the uniformity to obtain BCZY powder;

[0053] Note: The above mixture is pre-burned to eliminate the volatile components in the raw materials (such as nitrogen oxides NOx ) and promote the initial reaction to form a perovskite phase and a stable zirconia phase, in which the perovskite phase (BaCe0.7Zr0.2Y0.1O3- δ ) is mainly formed by the chemical reaction of barium source, cerium source, zirconium source and yttrium source. In addition, yttrium is doped into the zirconium oxide lattice to form a stable cubic phase structure. δ represents the amount of oxygen vacancies, and 3-δ is the proportion of actual oxygen atoms in the material. This is the conventional expression in the industry.

[0054] The mixture was first crushed and refined by a ball mill (until it passed a 200-mesh sieve) to ensure uniform mixing, and then pre-calcined at 900°C in air for 3 hours; the pre-calcined product was then ball-milled (until it passed a 300-mesh sieve) to further refine the particles and improve uniformity, thereby obtaining YSZ powder;

[0055] 3) Mix BCZY powder and YSZ powder in a mass ratio of 1:1 and mix them evenly using a ball mill to form a composite material precursor;

[0056] 4) The composite material precursor obtained in step 3) is pressed into a green body of a desired shape (e.g., 10 mm×10 mm×10 mm) by a molding method, and the formed green body is sintered in air at 1400° C. for 10 h to obtain a dense dual-phase electrolyte BaCe 0.7 Zr 0.2 Y 0.1 O3- δ @YSZ.

[0057] Note: The molding pressure is generally 100MPa~200MPa.

[0058] Experiment 1: Method 1 for synthesizing ammonia by electrochemical reduction of nitrogen:

[0059] A flat-plate solid oxide fuel cell (SOFC) is used. The flat-plate solid oxide fuel cell includes a cathode layer (Fe / YSZ), an anode layer (Ni / YSZ), and an electrolyte layer located between the cathode layer and the anode layer; the anode layer corresponds to the anode chamber of the battery, and the cathode layer corresponds to the cathode chamber of the battery; high-purity hydrogen (H2) is introduced into the anode chamber of the battery, and high-purity nitrogen (N2) is introduced into the cathode chamber of the battery. Hydrogen loses electrons at the anode to generate hydrogen ions, and the hydrogen ions react with the nitrogen in the cathode chamber through the electrolyte to generate NH3. The generated ammonia (NH3) is collected in the cathode chamber. That is, the gas in the cathode chamber (including unreacted nitrogen and generated ammonia) is discharged to the condensing device, and the ammonia is condensed into liquid or gaseous ammonia for collection. On the anode side, the residual hydrogen that does not participate in the electrochemical reaction can be directly discharged.

[0060] The electrolyte layer uses the dual-phase electrolyte BaCe obtained in Example 1 0.7Zr 0.2 Y 0.1 O3- δ Prepared by @YSZ.

[0061] The details are as follows:

[0062] The mixture in Example 1 was changed to nickel nitrate, and the rest was the same as Example 1. The obtained mixture was named Ni / YSZ and used as the anode layer material.

[0063] The mixture in Example 1 was changed to iron nitrate, and the rest was the same as Example 1. The obtained mixture was named Fe / YSZ and was used as the cathode layer material.

[0064] The BaCe prepared in Example 1 0.7 Zr 0.2 Y 0.1 O3- δ @YSZ was mixed with ethanol as a solvent at a solid-liquid ratio of 1 g:10 mL to obtain BCZY@YSZ composite electrolyte slurry.

[0065] The BCZY@YSZ composite electrolyte slurry was coated on an anode layer (Ni / YSZ) with a thickness of 20 μm, dried and sintered (dried at 80°C for 30 minutes and sintered at 800°C for 60 minutes) to form an electrolyte layer with a thickness of 10 μm; the above drying and sintering can ensure the density and uniformity of the electrolyte layer.

[0066] Fe / YSZ was mixed with ethanol as a solvent at a solid-liquid ratio of 1 g:10 mL to obtain a cathode catalyst slurry; the cathode catalyst slurry was coated on the other side of the electrolyte layer, dried and sintered (dried at 80°C for 30 minutes and sintered at 800°C for 60 minutes) to obtain a cathode layer with a thickness of 20 μm.

[0067] High-purity hydrogen (H2) was introduced into the anode chamber of the battery, and high-purity nitrogen (N2) was introduced into the cathode chamber of the battery. The flow rate and pressure were controlled (the flow rate of hydrogen and nitrogen was about 100 sccm, and the pressure was about 1.2 atm) to ensure a stable supply of gas. The battery was heated in a high-temperature furnace and kept at a constant temperature of 200°C. The voltage across the battery was controlled to be 1.5V using a power supply. The ammonia (NH3) generated was collected in the cathode chamber after continuous ventilation for 2 hours. The obtained reactant conversion rate was 98%, and the unit yield of the product was 200.6 μg h -1 .

[0068] Reactant conversion rate = actual nitrogen conversion / theoretical nitrogen conversion × 100%,

[0069] Unit yield of product = actual amount of ammonia produced / reaction time.

[0070] Experiment 2: Method 2 for synthesizing ammonia by electrochemical reduction of nitrogen:

[0071] In Experiment 1, change the voltage across the battery controlled by the power supply from "1.5V" to "1.2V", and the rest is the same as Experiment 1.

[0072] The BaCe prepared in Example 1 0.7 Zr 0.2 Y 0.1 O3- δ @YSZ Electrochemical synthesis of ammonia was carried out according to Experiment 2, and the obtained reactant conversion rate and product yield are described in Table 1 below.

[0073] Embodiment 2,

[0074] With respect to Example 1, the following changes are made:

[0075] Ba:Ce:Zr:Y=1:0.6:0.3:0.1 (molar ratio), barium nitrate, cerium nitrate, zirconium nitrate, and yttrium nitrate are mixed;

[0076] The pre-firing temperature of mixture 1 and mixture 2 was changed from "900°C" to "1000°C";

[0077] The rest is the same as Example 1.

[0078] Obtaining a dense two-phase electrolyte BaCe 0.6 Zr 0.3 Y 0.1 O3- δ @YSZ.

[0079] Embodiment 3,

[0080] With respect to Example 1, the following changes are made:

[0081] The mixing ratio (mass ratio) of BCZY powder and YSZ powder was changed from "1:1" to "2:1";

[0082] The rest is the same as Example 1.

[0083] Obtaining a dense two-phase electrolyte BaCe 0.7 Zr 0.2 Y 0.1 O3- δ @YSZ.

[0084] Embodiment 4,

[0085] With respect to Example 1, the following changes are made:

[0086] Change "sintering at 1400°C for 10 h" in step 4) to "sintering at 1500°C for 12 h";

[0087] The rest is the same as Example 1.

[0088] Obtaining a dense two-phase electrolyte BaCe 0.7 Zr 0.2 Y 0.1 O3- δ @YSZ.

[0089] The two-phase electrolytes obtained in Examples 2 to 4 were used to electrochemically reduce nitrogen to synthesize ammonia according to Experiment 1 and Experiment 2, respectively. The obtained reactant conversion rates and product yields are specifically described in Table 1 below.

[0090] Table 1

[0091]

[0092]

[0093] Comparative Example 1

[0094] With respect to Example 1, the following changes are made:

[0095] Eliminate the use of "Mixture II";

[0096] In step 3), only BCZY powder is mixed evenly using a ball mill; as a material precursor;

[0097] Step 4), pressing the material precursor obtained in step 3) into a green body of a desired shape by a compression molding method, and sintering the formed green body in air at 1500° C. for 12 hours;

[0098] The rest is the same as in Example 1;

[0099] Obtaining dense electrolyte BaCe 0.7 Zr 0.2 Y 0.1 O3- δ .

[0100] The BaCe prepared in Comparative Example 1 0.7 Zr 0.2 Y 0.1 O3- δ Electrochemical ammonia synthesis was carried out according to Experiment 2; the obtained reactant conversion rate was 68.5% and the product yield was 59.4 μg h -1 .

[0101] Comparative Example 2

[0102] With respect to Example 1, the following changes are made:

[0103] The mixing ratio (mass ratio) of BCZY powder and YSZ powder was changed from "1:1" to "1:10";

[0104] In addition, the step 4) is changed from "sintering at 1400°C for 10 h" to "sintering at 1500°C for 12 h".

[0105] The rest is the same as Example 1.

[0106] Obtaining a dense two-phase electrolyte BaCe 0.7 Zr 0.2 Y 0.1 O3- δ @YSZ

[0107] The BaCe prepared in Comparative Example 2 0.7 Zr 0.2 Y 0.1 O3- δ @YSZ Electrochemical ammonia synthesis was carried out according to Experiment 2; the obtained reactant conversion rate was 64.2% and the product yield was 53.5 μg h -1 .

[0108] Finally, it should be noted that the above examples are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.

Claims

1. A two-phase solid electrolyte for electrochemical reduction of nitrogen to synthesize ammonia, characterized in that The steps include: 1) According to the molar ratio of Ba:Ce:Zr:Y=1:x:y:1-xy, barium nitrate, cerium nitrate, zirconium nitrate and yttrium nitrate are uniformly mixed to obtain a mixture 1; x=0.1-0.9, y=0.1-0.9; According to Y2O3:ZrO2=7-9mol%, Y2O3 is added into ZrO2 and mixed evenly to obtain a second mixture; 2) The mixture is crushed and pre-calcined in air at 900-1000°C for 3-5h to obtain BCZY powder; The mixture is crushed and calcined in air at 900-1000°C for 3-5h to obtain YSZ powder; 3) Mix BCZY powder and YSZ powder in a mass ratio of 1-5:5-1 to form a composite material precursor; 4) The composite material precursor is molded into a green body, and then the molded green body is sintered in air at 1400-1500° C. for 10-12 hours to obtain a dual-phase solid electrolyte.

2. The dual-phase solid electrolyte according to claim 1, characterized in that: x=0.6~0.7, y=0.2~0.3; BCZY powder:YSZ powder = mass ratio of 1 to 2:

1.

3. The dual-phase solid electrolyte according to claim 1 or 2, characterized in that: In step 1), the molar ratio of Ba:Ce:Zr:Y=1:0.7:0.2:0.1; Y2O3:ZrO2=8 mol%; In step 2), the mixture 1 is crushed and pre-fired in air at 900° C. for 3 h, and the mixture 2 is crushed and pre-fired in air at 900° C. for 3 h.

4. The dual-phase solid electrolyte according to any one of claims 1 to 3, characterized in that: The pressure of compression molding is 100MPa to 200MPa.

5. A method for synthesizing ammonia by electrochemical reduction of nitrogen, using a flat solid oxide fuel cell, the flat solid oxide fuel cell comprising a cathode layer, an anode layer and an electrolyte layer located between the cathode layer and the anode layer; the anode layer corresponds to the anode chamber of the battery, and the cathode layer corresponds to the cathode chamber of the battery; high-purity hydrogen is passed into the anode chamber, high-purity nitrogen is passed into the cathode chamber, and the generated ammonia is collected in the cathode chamber; characterized in that: The material of the electrolyte layer is the dual-phase solid electrolyte obtained in claims 1 to 4; The battery is heated and kept warm to 200-500°C, and the voltage range across the battery is controlled to be 0-2.0V.

6. The method for synthesizing ammonia by electrochemical reduction of nitrogen according to claim 5, characterized in that: The material of the anode layer is Ni / YSZ; the material of the cathode layer is Fe / YSZ.

7. The method for synthesizing ammonia by electrochemical reduction of nitrogen according to claim 5 or 6, characterized in that: The thickness of the anode layer is 18 to 22 μm, the thickness of the electrolyte layer is 9 to 11 μm, and the thickness of the cathode layer is 18 to 22 μm; The flow rates of hydrogen and nitrogen are both 80-120 sccm, and the pressures are both 1.1-1.3 atm.

8. The method for synthesizing ammonia by electrochemical reduction of nitrogen according to claim 7, characterized in that: The dual-phase solid electrolyte is prepared into a slurry, coated on the anode layer, dried and sintered to form an electrolyte layer; then Fe / YSZ is prepared into a slurry and coated on the other side of the electrolyte layer, dried and sintered to form a cathode layer.

Citation Information

Patent Citations

  • High-entropy solid oxide fuel cell and preparation and application thereof

    CN115050978A

  • Method of preparing yttrium oxide stable zirconium oxide electrolyte film

    CN1753222A

  • Proton conductor for electrolyte of solid oxide fuel cells and solid oxide fuel cells comprising same

    KR1020130022828A

  • Co-doped YSZ electrolytes for solid oxide fuel cell stacks

    US20100167170A1

  • Method for manufacturing protonic ceramic fuel cells

    US20180331381A1